(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Globalization and the Indian legal profession, it examines the impact of globalization on Indianadvocates and legal practitioners both within and outside the country’s borders. According to the study,foreign laws have an impact on advocacy in India, as well as on advocates practicing law in the country.The impact on our economy as a whole of the globalization of the legal profession, Because of the paper’sfocus on the disparity between current and previous ideas and purposes of legal education, as well asthe altered legal profession as a result of globalization, an advocate’s role in delivering legal aidservices is critical to our economy’s ability to run properly. When it comes to sustaining and bridge thegaps between the civilizations, advocates have played an important part. They also try their best toprovide justice for those who truly deserve. The influence of the World Trade Organization andglobalization on the judicial system, as well as the issues encountered by the legal system in India andinternationally.